Supplementary data about the species Echinochaete russiceps (Berk. & Br.) Reid (Basidiomycetes) in Vietnam - Tham, Le Xuan (Academia Journal of Biology, 2014)
Echinochaete russiceps (Berk. & Br.) Reid (Basidiomycetes), just namely mentioned in the macrofungi of Vietnam, was supplemented in this paper with the first collection of authentic specimens newly-recorded, described and illustrated in details from the Cattien national park, Dongnai province, South Vietnam. This species was similar to Polyporus species in macro-morphological features, but had segregated characteristics as following: specific setoid elements in form of thick-walled yellow brown lanceolates and spines on the upper surfaces of pilei and in the hymenium-on the pore surfaces, and with gelatinous layer in the context excreted outside of matured fruitbodies.